2019
DOI: 10.26502/avsm.005
|View full text |Cite
|
Sign up to set email alerts
|

Macroanatomic structure and morphometric analysis of middle ear in ostrich (Struthio camelus)

Abstract: Ostrich (Struthio camelus) is a species belonging to the Struthionidae family of Struthioniformes order that does not have the flying ability among birds. The aim of this study was to make a subgross investigation on anatomical structures of middle ear in ostrich and to determine the morphometry of the columella.In the present study, 4 adult ostrich heads were used in the study. Tympanic cavity and the formations inside are removed from the skull by protecting the cranial roof. Subgross examinations of tympani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…As mentioned earlier, the presence of the three‐ossicle assembly is described in mammals (Amin & Tucker, 2006; Takechi & Kuratani, 2010) while a special situation is reported for birds, where a single ossicle is described—the Columella auris (Anthwal, Joshi, & Tucker, 2013; Beșoluk, Orhun Dayan, Eken, Turgut, & Aydogdu, 2019; Claes et al., 2017; Mills, 1994; Takechi & Kuratani, 2010). In reptiles, the same bony piece is reported as the stapes (Anthwal et al., 2013).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…As mentioned earlier, the presence of the three‐ossicle assembly is described in mammals (Amin & Tucker, 2006; Takechi & Kuratani, 2010) while a special situation is reported for birds, where a single ossicle is described—the Columella auris (Anthwal, Joshi, & Tucker, 2013; Beșoluk, Orhun Dayan, Eken, Turgut, & Aydogdu, 2019; Claes et al., 2017; Mills, 1994; Takechi & Kuratani, 2010). In reptiles, the same bony piece is reported as the stapes (Anthwal et al., 2013).…”
Section: Introductionmentioning
confidence: 91%
“…Thanks to its important integrative function, present‐day research for middle ear structure was reported for several species such as the chinese bamboo rat (Pleštilová, Hrouzková, Burda, & Šumbera, 2016), toad (Womack, Stynoski, Voyles, Coloma, & Hoke, 2018), rabbit (Guan et al., 2019), pig (Pracy, White, Mustafa, Smith, & Perry, 1998), miniature pigs (HaiJin et al., 2013), humans, (Arechvo et al., 2013; Isaacson, 2014; Luers & Hüttenbrink, 2016; Sawada, Nara, Fukui, Dodo, & Hirata, 2014; Stieger, Djeric, Kompis, Remonda, & Häusler, 2006; Whyte et al., 2001) other primates, moles (Mason, 2006), dog (Berghes, Parvu, Cucoanes, & Cuca, 2010; Ortug & Türkmenoğlu, 2005), Indian mangoose (Kamali, Gholami, Ahrari‐Khafi, Rasouli, & Shayegh, 2015), horse, cat, cow, rat, mouse (Amin & Tucker, 2006; Blanke, Aupperle, Seeger, Kubick, & Schusser, 2015; Botti, Secci, Ragionieri, Dessole, & Acone, 2006; Mohammadpour, 2010) or other extinct rodents (Lange, Stalleicken, & Burda, 2004), hamster, gerbil, New Zeeland rabbit (Kurtul, Cevik, Bozkurt, & Dursun, 2003), ostrich (Beșoluk et al., 2019; Keenan, Mears, & Skedros, 2017), degu (Argyle & Mason, 2008), weasel or chinchilla (Bergin, Vlajkovic, Bird, & Thorne, 2013; Carrasco, Maass, Dentone, Miranda, & Kukuljan, 2008; Charuta et al., 2011; Hoffstetter et al., 2011; Maier, Tröscher, & Ruf, 2018; Maravilla et al., 2011; Martonos et al., 2019; Rodrigues, Shinohara, Andreo, Buchaim, & Ahmed, 2012; Wang & Gan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed values for several parameters of the auditory ossicles, as well as weight parameters and area measurements for the tympanic membrane, and the oval and round window. Similar morphological studies on the middle ear structures were performed on carnivores, such as wolves [ 10 ], dogs [ 16 , 17 ], badgers [ 18 ], red foxes, dogs and cats [ 4 ], on domestic and wild carnivores [ 19 ], on some herbivores, such as goats [ 20 ], sheep [ 21 ], horses [ 22 ], donkeys [ 23 , 24 ], on ruminants [ 25 ], on rodents, such as mice [ 26 ], hamsters [ 27 ], rabbits [ 9 , 28 ], chinchillas [ 29 , 30 ], and on some birds, such as ostriches [ 31 ] and chickens [ 32 ]. Geometric morphometry provides more precise information about small anatomical structures and focuses on data analysis from the position of homologous landmarks [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The malleo-incal complex is also implicated in specific cases of humans and mice as a probable explanation for deafness [ 53 ]. The total absence of the incus has also been cited in birds [ 33 , 57 , 58 , 59 , 60 , 61 ] and some reptiles [ 33 , 57 , 62 ].…”
Section: Discussionmentioning
confidence: 99%